1993
DOI: 10.1007/bf00685833
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antitumor activity of mitomycin C in vitro and in vivo by UCN-01, a selective inhibitor of protein kinase C

Abstract: UCN-01 (7-hydroxy-staurosporine) is a potent and selective inhibitor of protein kinase C (PKC), one of several protein kinases examined. UCN-01 itself was shown to exhibit antitumor activity in vitro and in vivo in oncogene-activated human and murine tumor cell lines. Since the mechanism(s) of action of UCN-01 is thought to be different from those of alkylating agents, including mitomycin C (MMC), we tested the combined effect of UCN-01 with MMC on human epidermoid carcinoma A431 cells. UCN-01 potentiated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 13 publications
1
55
0
1
Order By: Relevance
“…As a modulator, UCN-01 enhances the antitumour activity of several antitumour agents, including mitomycin C (Akinaga et al, 1993), cisplatin (Bunch and Eastman, 1996;Husain et al, 1997) and 5-FU both in vitro (Abe et al, 2000) and in vivo (Koh et al, 2002). The potentiation of cytotoxicity by UCN-01 is ascribed to its ability to abrogate the G2/M checkpoint Wang et al, 1996), as previously reported for caffeine (Powell et al, 1995;Fan et al, 1997).…”
Section: Introductionsupporting
confidence: 54%
“…As a modulator, UCN-01 enhances the antitumour activity of several antitumour agents, including mitomycin C (Akinaga et al, 1993), cisplatin (Bunch and Eastman, 1996;Husain et al, 1997) and 5-FU both in vitro (Abe et al, 2000) and in vivo (Koh et al, 2002). The potentiation of cytotoxicity by UCN-01 is ascribed to its ability to abrogate the G2/M checkpoint Wang et al, 1996), as previously reported for caffeine (Powell et al, 1995;Fan et al, 1997).…”
Section: Introductionsupporting
confidence: 54%
“…Moreover, MCF-7 cell lines harboring no endogenous p53 due to ectopic expression of the human papillomavirus type-16 E6 protein, showed enhanced cytotoxicity with the combination between DNA-damaging agents, such as cisplatin and UCN-01, compared with the isogenic wild type MCF-7 cell line. This synergistic e ect of UCN-01 was also observed with mitomycin C, 5-ÂŻuoruracil, BCNU, camptothecin, among others (Akinaga et al, 1993;Bunch and Eastman, 1996;Hsueh et al, 1998;Husain et al, 1997;Pollack et al, 1996;Shao et al, 1997;Tsuchida and Urano, 1997). Therefore, it is likely that this preclinical information may guide us in the clinical development of UCN-01 as a modulator of standard chemotherapy in the clinic Wilson et al, 2000).…”
Section: Ucn-01mentioning
confidence: 68%
“…The potent Chk1/Chk2 inhibitor AZD7762 is under phase I, dose-escalation study to evaluate the safety, pharmacokinetics (PK) and preliminary efficacy alone or in combination with gemcitabine in Japanese patients with advanced solid malignancies (Seto et al, 2013). Similarly, other CHK1 inhibitors including PF-477736 (Pfizer) and SCH900776 (Schering Plough) are also under Phase I or II clinical evaluation in patients (Ashwell et al, 2008;Karp et al, 2012 (Mizuno et al, 1995) Chk1 (Busby et al, 2000) Mytomycin C (Akinaga et al, 1993) Cisplatin (Bunch and Eastman, 1996) Topoisomerase I poisons (Tse et al, 2007a) Gemcitabine (Shi et al, 2001) Phase I/ II Gö6976 PKCïĄï€ (Martiny-Baron et al, 1993…”
Section: Figure16 Schematic Representation Of the Effect Of Chk1 Onmentioning
confidence: 99%